2014
DOI: 10.1371/journal.pone.0090137
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Mode Action of Mangiferin in Mouse Liver under High Fat Diet

Abstract: Chronic over-nutrition is a major contributor to the spread of obesity and its related metabolic disorders. Development of therapeutics has been slow compared to the speedy increase in occurrence of these metabolic disorders. We have identified a natural compound, mangiferin (MGF) (a predominant component of the plants of Anemarrhena asphodeloides and Mangifera indica), that can protect against high fat diet (HFD) induced obesity, hyperglycemia, insulin resistance and hyperlipidemia in mice. However, the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 62 publications
(65 reference statements)
3
45
0
2
Order By: Relevance
“…Scd1 catalyzes the conversion of stearoyl‐CoA to oleoyl‐CoA, which is a major substrate for TG synthesis. Ingenuity pathway analysis (IPA) of these proteomics data predicted that MGF suppressed SREBPs . This data corroborates a report by Guo et al showing that MGF treatment in hamster resulted in reduced SREBP‐1c transcripts in liver .…”
Section: Mgf Inhibits Hyperlipidemia and Prevents Nafldsupporting
confidence: 88%
See 1 more Smart Citation
“…Scd1 catalyzes the conversion of stearoyl‐CoA to oleoyl‐CoA, which is a major substrate for TG synthesis. Ingenuity pathway analysis (IPA) of these proteomics data predicted that MGF suppressed SREBPs . This data corroborates a report by Guo et al showing that MGF treatment in hamster resulted in reduced SREBP‐1c transcripts in liver .…”
Section: Mgf Inhibits Hyperlipidemia and Prevents Nafldsupporting
confidence: 88%
“…We recently provided evidence that MGF activates PDH . Our proteomics study also predicts other molecular targets and signaling pathways affected by MGF . While these studies advanced our understanding of the mechanisms of action of MGF, more mechanistic studies are in great need to provide clear pictures of how MGF exerts its beneficial effects.…”
Section: Discussionmentioning
confidence: 87%
“…The effect may be due to the active molecule MGF, which is present in our mango fruit powder [18]. It has been reported that MGF may ameliorate high-fat diet-induced hepatic TG accumulation and may decrease FFA and TG while increasing plasma beta-hydroxybutyrate levels in rodents [37-39], partly by modulating the expression of genes involved in lipid oxidation and mitochondrial bioenergetics in key metabolic tissues [37-40]. In a randomized, double-blind, controlled trial in humans, MGF supplementation (150 mg/day 12 weeks) improved serum lipid profiles in overweight patients with hyperlipidemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, it signifi cantly increased the levels of proteins important for mitochondrial biogenesis and oxidative activity, including oxoglutarate dehydrogenase E1 and cytochrome c oxidase subunit 6B1, and decreased the levels of those critical for lipogenesis, such as fatty acid stearoylCoA desaturase 1 and acetyl-CoA carboxylase 1 (Lim et al 2014 ).…”
Section: Antidiabetic Effect In Kk-a Y Diabetic Model Streptozotocinmentioning
confidence: 99%